2008
DOI: 10.1128/jcm.02241-07
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Method of Collection of First-Void Urine for Diagnosis of Chlamydia trachomatis Infection in Men

Abstract: First-void urine (FVU) is the preferred specimen for the diagnosis of urogenital Chlamydia trachomatis infection in men. We have developed FirstBurst, a urine collection device that collects the first 4 to 5 ml of FVU and yields a specimen with a sixfold higher C. trachomatis organism load than the regular urine cup by quantitative PCR (32,533 versus 5,271 plasmids/ml; P < 0.0001). Consequently, the use of FirstBurst to collect a urine sample improved the sensitivity of a rapid test for Chlamydia over testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 13 publications
0
51
0
3
Order By: Relevance
“…Four publications on CRT performance authored between 2007 and 2009 reported CRT sensitivities for male ‘First Burst’ urine between 82% and 82.6%,17 19 and for CRT female vaginal swabs between 71% and 86.8%;20 21 a systematic review of these studies reported pooled estimates of CRT sensitivity and specificity for male first-void urine specimens to be 77% and 99%, and for female vaginal swabs to be 80% and 99% 22…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four publications on CRT performance authored between 2007 and 2009 reported CRT sensitivities for male ‘First Burst’ urine between 82% and 82.6%,17 19 and for CRT female vaginal swabs between 71% and 86.8%;20 21 a systematic review of these studies reported pooled estimates of CRT sensitivity and specificity for male first-void urine specimens to be 77% and 99%, and for female vaginal swabs to be 80% and 99% 22…”
Section: Discussionmentioning
confidence: 99%
“…The First Burst yields an approximately sixfold higher organism load per mL of urine than a routine cup-collected specimen 17. Where two samples were collected for CRT and ACON, collection order was alternated.…”
Section: Methodsmentioning
confidence: 99%
“…In men with urethral discharge, a urethral swab was collected for chlamydia, gonorrhoea and T. vaginalis. In men without urethral discharge, a first-void urine specimen (or a sample no less than 3 h after previous micturition) 22 was collected for the detection of these STIs. A 10-mL venepuncture blood specimen was collected at baseline and scheduled clinical follow-up visits for syphilis and herpes simplex virus Type 2 (HSV-2).…”
Section: Study Design and Proceduresmentioning
confidence: 99%
“…The time point of urine collection during micturition may significantly affect the urinary composition, mainly due to bacterial contamination. A mid-stream urine sample is usually favored, except when studying urinary tract infections where first-void volume is preferred [36,37]. Finally, in large-scale human metabolomics studies, samples are frequently collected at different sites.…”
Section: Sampling Conditionsmentioning
confidence: 99%